Practical Fluorescence Spectroscopy - Gryczynski, Zygmunt (Boca Raton : CRC Press LLC, 2019)
Presenting a detailed, hands-on approach to fluorescence spectroscopy, this book describes experiments that cover basic spectroscopy and advanced aspects of fluorescence spectroscopy. It emphasizes practical guidance, providing background on fundamental concepts as well as guidance on how to handle artifacts, avoid common errors, and interpret data. Nearly 150 experiments from biophysics, biochemistry, and the biomedical sciences demonstrate how methods are applied in practical applications. The result is a hands-on guide to the most important aspects of fluorescence spectroscopy, from steady-state fluorescence to advanced time-resolved fluorescence. Provides a complete overview of nearly 150 experiments using fluorescence spectroscopy, from basic to advanced applications Presents laboratory methods using a variety of instrumental setups with detailed discussion of data analysis and interpretations Covers steady-state phenomena, time-resolved phenomena, and advanced methods Spans biophysical, biochemical, and biomedical applications Describes related concepts, theory, and mathematical background as well as commercially available instruments used for measurements
Experiment 3-8 Absorbance of Rhodamine 800-Effect of Out of Range Absorption -- Experiment 3-9 Absorbance of Anthracene-Low Absorption Range -- Experiment 3-10 Low Absorbance-How to Improve Quality of Measured Spectrum -- Experiment 3-11 Absorbance of Rhodamine B-Proper Use of Cuvettes -- Experiment 3-12 How to Adopt a Fluorescence Cuvette for Absorbance Measurement -- Experiment 3-13 Determining the Concentration of Chromophores in a Solution from Known Optical Density (Absorption) -- Experiment 3-14 Absorbance of Benzene-Resolvable Vibrionic States
Description based upon print version of record.
Experiment 3-15 Measuring the Transmission of Filters
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Biochemistry; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Physics; Fluorescence spectroscopy